Effects of a social-media-based support on premenstrual syndrome and physical activity among female university students in South Korea - Su Jin Nam; Chiyoung Cha (Taylor & Francis Group, 2020)
Introduction: This study examined the effects of social-media-based support on premenstrual syndrome (PMS) and physical activity among female South Korean university students. Methods: This quasi-experimental study with an equivalent-control-group pretest-posttest design randomly assigned 64 female students with PMS to the experimental or control group. The experimental group received social-media-based support through a smartphone application, text messaging, and e-mail for one menstrual cycle between September and December, 2016. Descriptive and inferential statistics included a Chi-square test and independent and paired t-tests. Results: Significant differences emerged between the experimental and control groups in total PMS scores (p = .003), 14 premenstrual symptoms, and physical activity (p = .010). Conclusions: Female university students with PMS experienced decreased premenstrual symptoms and increased physical activity with social-media-based support, which could be an efficacious, accessible, and widely available nursing intervention to manage PMS and physical activity.